Pengaruh Pemberian Tepung Daun Indigofera (Indigofera tinctoria) sebagai pengganti bungkil dalam ransum terhadap kandungan nutrisi daging ayam Kampung Unggul Balitnak (KUB). : NUTRIENT LEVELS OF KUB CHICKEN MEAT FED INDIGOFERA MEAL AS A SUBSTITUTE FOR SOYBEAN MEAL (Jurnal Peternakan Nusantara, 2022)
Soybean meal is one of the main feeds used in commercial poultry rations. However, this feed is relatively expensive as most of it is still imported.  Indigofera leaf meal (ILM), with its good nutrient content and relatively low cost, is a potential feed to be used as a substitute for soybean cake meals.  This study aimed to assess the meat nutrient contents of KUB chickens fed a ration containing ILM as a substitute for soybean  meals.  The study was conducted in Nambo Peuntas, Sukajaya Village, Taman Sari District, Bogor Regency, West Java, from 1 April to 15 June 2021.  One hundred unsexed one-day-old KUB chickens were allocated into five treatments and four replicates in a completely randomized design.  Treatments consisted of the substitution of soybean cake meal with ILM by 0% (R0, control), 25% (R1), 50% (R2), 75% (R3), and 100% (R4).  Measurements were taken on meat protein, fat, water, and ash contents.  Data were subjected to an analysis of variance and a Duncan test.  Results showed that substituting soybean cake meals with ILM could maintain the meat nutrient contents of KUB chickens.